1983
DOI: 10.1159/000238212
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Activity of Pretazettine, Standard Drugs, and the Combinations on Intraperitoneally Implanted Lewis Lung Carcinoma in Mice

Abstract: Therapeutic effectiveness of pretazettine (PTZ) has been demonstrated in the intraperitoneally (i.p.) implanted Lewis lung carcinoma (LLC) in both syngeneic and allogeneic mice. The i.p. implanted LLC has been found to be sensitive to most standard drugs tested such as cyclophosphamide (CY), actinomycin D, 5-fluorouracil, methotrexate, 6-thioguanine and vincristine, in comparison to the subcutaneously (s.c.) or intravenously (i.v.) implanted LLC which was reported to be resistant to most standard drugs (s.c.-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…We found that therapeutic administration of CY at moderate doses (0.5-1 mg/mouse) enhanced the growth of LLC [3,4], Giraldi et al [8] also reported that the therapeutic administration of CY at. a daily low dose (0.3 mg/mouse/day x 8) resulted in increased lung metastasis of LLC.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We found that therapeutic administration of CY at moderate doses (0.5-1 mg/mouse) enhanced the growth of LLC [3,4], Giraldi et al [8] also reported that the therapeutic administration of CY at. a daily low dose (0.3 mg/mouse/day x 8) resulted in increased lung metastasis of LLC.…”
Section: Discussionmentioning
confidence: 78%
“…Previously, we demonstrated that therapeutic ad ministration of cyclophosphamide (CY) at moderate doses (25-50 mg/kg) was not effective but promoted the growth of LLC [3,4], The adverse tumor-enhanc ing phenomenon was probably due to the strong im munosuppressive action of CY which overcame the cytoreductive action [4]. The antitumor activity of some cytotoxic drugs such as adriamycin, BCNU, actinomycin D, 5-FU, and methotrexate was almost abolished when CY was combined [4], Now, we have tested the antitumor effect of Viva-Natural in CYtreated mice and compared with two standard immu nomodulators, isoprinosine and MVE-2.…”
Section: Effect O F Viva-natural On Intraperitoneally Implanted Llc Imentioning
confidence: 99%
“…The optimal dose of standard cytotox ic drugs for combination in the intraperitoneally im planted LLC system has already been established [2], Immediately after a single intraperitoneal injection of standard drugs at optimal doses, daily injection of Viva-ppt at a dose of 50 mg/kg i.p. was commenced and continued for 7 days.…”
Section: Effect O F Viva-natural In Combination With Standard Drugs Omentioning
confidence: 99%
“…We have earlier described the isolation and charac terization of the active principles of narcissus bulbs [1,2] as a result of our screening plant materials of the Pacific area. Now we have found an agent active against Lewis lung carcinoma (LLC) present in Un daria pinnantifida, a popular dietary seaweed.…”
Section: Introductionmentioning
confidence: 99%
“…During antiviral screening of medicinal plants of the Pacific area, we found pre tazettine hydrochloride (PTZ), a narcissus alkaloid, to be active against Rauscher vi ral leukemia and spontaneous AKR leu kemia [1,2], PTZ is a specific inhibitor of cellular protein synthesis and is also effec tive against intraperitoneally implanted Lewis lung carcinoma (LLC) and Ehrlich ascites tumor, both non-viral transplan table tumors [3,4], In contrast to the intraperitoneally implanted LLC, which is moderately sensitive to many standard cytotoxic drugs [3], LLC implanted subcu taneously in the syngeneic or semi-syn geneic mice is highly resistant to chemo therapy [5,6]. This paper describes the ef fectiveness of PTZ, standard drugs, and combinations of both, against the subcu taneously implanted LLC in syngeneic and allogeneic mice.…”
Section: Introductionmentioning
confidence: 99%